Efektifitas Sosialisasi Supervisi 4S dalam Rangka Peningkatan Budaya Keselamatan Pasien: Effectiveness of Socialization 4S Supervision to Improve Patient Safety Culture - Arif, Yulastri; Khairina, Ilfa; Susmiati, Susmiati; Nelwati, Nelwati; Puteri, Zifriyanthi Minanda; Ananda, Yuanita; Murni, Dewi; Sidaria, Sidaria; Muthmainnah, Muthmainnah; Maisa, Esthika Ariany (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Healthcare facilities must adhere to patient safety principles to reduce the risk of harm. Prof. Dr. M.A. Hanafiah SM Batusangkar Hospital is among the healthcare providers in West Sumatra, necessitating endeavors to enhance and sustain service quality, especially regarding patient safety. The effectiveness of the patient safety culture depends on the 4 S supervision elements, including Structure, Skill, Support, and Sustainability. The 4S supervision model guides and aids nurses in advancing their skills related to patient safety. Survey findings at the hospital revealed that the promotion of 4S supervision was suboptimal, manifesting as nurses' limited grasp of the concept. On July 28-29, 2023, a structured socialization, education, and mentorship program was conducted for nursing executives and managers. The objective was to empower nurses to incorporate multilayered supervision into patient care and oversee the implementation of patient safety in inpatient, outpatient, and emergency room settings, aiming to enhance the patient safety culture.